Multimedia Development Life Cycle Method in Designing Interactive Learning Media for Introducing Basic Religious Knowledge at the Quran Learning Center - Khasanah, Fata Nidaul (Greenation International Journal of Engineering Science, 2024)
Education is a crucial element in shaping an individual's character and abilities, especially from an early age. In one Quran Learning Center (TPA), the learning process still faces challenges due to a lack of varied teaching methods, which reduces children's understanding of essential subjects such as the Pillars of Islam, the Pillars of Faith, and the Arabic alphabet (Hijaiyah). This study aims to develop and implement an interactive learning medium based on Adobe Flash as an innovative solution to enhance the quality of learning at TPA. The research method used is the Multimedia Development Life Cycle (MDLC). The developed learning medium integrates visual, audio, and interactive features such as animations and quizzes, creating an engaging and enjoyable learning environment for children. The research findings indicate that the designed application meets the expected results in its functional testing. Furthermore, during the distribution stage, the application was exported in *.exe format, making it easy to use on computer devices.